Pemberdayaan Masyarakat melalui Usaha Home Industry Pengelolaan Karung Bekas di Desa Dukuhmencek Kabupaten Jember - Mohammad Fahmi Arif; Febrina Rizky Agustina (Jurnal Al-Hikmah, 2022)
Many times, most empty used sacks are only burned and thrown away which then becomes environmental problem. However, in Dukuhmencek village, Sukorambi District, Jember Regency there is an unnoticed community empowerment activity through manufacturing used sacks as a home industry. This community empowerment activity is carried out to provide knowledge to the community that used sacks still can be reused and recycled. Through focusing on manufacturing used sacks, the goal is to prosper the community by creating job opportunities for the community, reduce poverty by helping the family’s economy, and reduce environmental damage. The focus of this research is divided into three, namely: 1) How is the process of community empowerment through manufacturing used sacks as a home industry, 2) What are the inhibiting factors for community empowerment through manufacturing used sacks as a home industry and 3) What is the impact of community empowerment through manufacturing used sacks as a home industry. The current study is qualitative research with a descriptive approach and a purposive sampling method was employed to choose the research subjects. The data was gathered through observation, interviews and documentation techniques. Source triangulation, technique triangulation and time triangulation were employed to verify the data. The results showed that the manufacturing used sacks as a home industry could be clarified a s community empowerment activity.